Western Europe through the Eyes of Students of Kazakhstan Universities: Countries’ Images and Driving Force for their Formation - Aigul’ Begenovna Yessimova; Sergei Alekseevich Panarin (Vestnik RUDN. International Relations, 2019)
The image of a country, and especially how the country is viewed from beyond its borders, is becoming an increasingly important resource capable of exerting positive or negative influence in various fields, including international relations. In the USSR, Western Europe was endowed with a dual image of cultural treasury and the territory dominated by classes and forces hostile to the socialist camp. After the collapse of the USSR, Western Europe began to be perceived as a capitalist model to be coped, and it is from those years that the contemporary ideas of the youth in Kazakhstan about its image have being originated. In order to probe them, a pilot sociological survey was conducted in two Kazakhstani universities, one of which is located in the north-east of the country, in the city of Ust’-Kamenogorsk, the second is in the south, in Shymkent. The results obtained allow us to assert with confidence that students do not have a holistic image of Western Europe; their views are dominated by images of individual European countries, and these images differ greatly in the degree of completeness. The most developed images are those of France and Germany, but even they represent no more than a set of widespread stereotypes about the economic, political, cultural characteristics of both countries. It is also striking that the images of Western European countries, which emerge from the students’ answers, are generally deprived of any meaningful and easily recognizable embodiment, i.e. they are very rarely identified with historically, politically and culturally significant personalities. According to the authors, this feature indicates that students view Western Europe most and foremost as a place where their various consumer needs can be satisfied.